Feasibility Analysis Of Financing Subsidized Mortgage Customers At Bank Btn Syariah Makassar Branch - Herman, Nur Melianda (ADPEBI, 2022)
Banking institutions have an essential role in the development and economy of a country so that banks become agents of product to realize national development goals with the standard of living of the Indonesian people and create economic growth. To channel financing, Islamic Banks have considerations before providing funding to customers. A handful of people still provide data that does not match the facts on the ground. This makes the financing not feasible to be given. This study uses a qualitative method. They are using a data analysis approach using the 5C+1S principle. The study results found that Bank BTN Syariah Makassar Branch principle 5C + 1S in conducting customer financing feasibility analysis. Character, Capacity and Collateral are these three points that influence the ongoing financing. Meanwhile, capital and conditions of the economy are only supporting aspects because both of them do not have a significant influence in the process of providing funding, while in Sharia, namely 1 S, more emphasis is placed on the sale and purchase contract, where this Islamic bank prioritizes MUI fatwa decisions and must meet Sharia elements.